Hallmarks of Retroelement Expression in T-Cells Treated With HDAC Inhibitors - Curty, Gislaine; Iñiguez, Luis P.; Nixon, Douglas F.; Soares, Marcelo A.; de Mulder Rougvie, Miguel (Frontiers in Virology, 2021)
A wide spectrum of drugs have been assessed as latency reversal agents (LRA) to reactivate HIV-1 from cellular reservoirs and aid in viral eradication strategies. Histone deacetylase inhibitors (HDACi) have been studied in vitro and in vivo as potential candidates for HIV-1 latency reversion. Suberoylanilide hydroxamic acid (SAHA) and romidepsin (RMD) are two HDACi able to reverse HIV latency, however studies of potential off-target effects on retroelement expression have been limited. Retroelements constitute a large portion of the human genome, and some are considered “fossil viruses” as they constitute remnants of ancient exogenous retroviruses infections. Retroelements are reactivated during certain disease conditions like cancer or during HIV-1 infection. In this study, we analyzed differential expression of retroelements using publicly available RNA-seq datasets (GSE102187 and GSE114883) obtained from uninfected CD4+, and HIV-1 latently infected CD4+ T-cells treated with HDACi (SAHA and RMD). We found a total of 712 and 1,380 differentially expressed retroelements in HIV-1 latently infected cells following a 24-hour SAHA and RMD treatment, respectively. Furthermore, we found that 531 retroelement sequences (HERVs and L1) were differentially expressed under both HDACi treatments, while 1,030 HERV/L1 were exclusively regulated by each drug. Despite differences in specific HERV loci expression, the overall pattern at the HERV family level was similar for both treatments. We detected differential expression of full-length HERV families including HERV-K, HERV-W and HERV-H. Furthermore, we analyzed the link between differentially expressed retroelements and nearby immune genes. TRAF2 (TNF receptor) and GBP5 (inflammasome activator) were upregulated in HDACi treated samples and their expression was correlated with nearby HERV (MERV101_9q34.3) and L1 (L1FLnI_1p22.2k, L1FLnI_1p22.2j, L1FLnI_1p22.2i). Our findings suggest that HDACi have an off-target effect on the expression of retroelements and on the expression of immune associated genes in treated CD4+ T-cells. Furthermore, our data highlights the importance of exploring the interaction between HIV-1 and retroelement expression in LRA treated samples to understand their role and impact on “shock and kill” strategies and their potential use as reservoir biomarkers.